Pengembangan Peta Profil Desa untuk Mendukung Pembangunan Berkelanjutan Desa Sumberahayu, Kecamatan Limbangan, Kabupaten Kendal - Alfita Ilfiyaningrum; Arief Kusbiantoro; Arie Taveriyanto; M. Faizal Ardhiansyah Arifin; Agung Sutarto; Bambang Hariyadi; Nur Aida; Amelia, Naswa Badi; Ahmad Ali Adnan; Yora Trista Gracia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The village profile map is an essential instrument for sustainable development planning as it provides comprehensive spatial and non-spatial data. Sumberahayu Village, located in Limbangan District, Kendal Regency, has significant potential in terms of natural and human resources; however, it lacks integrated data to support effective development decision-making. This community service program aims to develop a village profile map as a foundation for data-driven development planning. The methodology involved literature review, field surveys, collection of primary and secondary data, terrestrial measurements, utilization of remote sensing data, and data processing using Geographic Information System (GIS) software. The final result is a village profile map of Sumberahayu that includes information on administrative boundaries, infrastructure distribution, local resource potential, land use, and disaster-prone areas. This map is expected to serve as a strategic planning tool for village governments in asset management, disaster mitigation, and sustainable local economic development.